Determination of the influence of aluminum phosphate on the properties of quartz ceramics - Karasik, Olena; Kozyreva, Tatyana; Dushyn, Vladyslav (Eastern-European Journal of Enterprise Technologies, 2021)
One of the significant disadvantages of quartz glass-based materials is their tendency to crystallize cristobalite during firing and, as a consequence, a significant deterioration in performance. In order to prevent crystallization of quartz ceramics during sintering, a number of additives are used. However, all known options some disadvantages, namely, relatively low strength values and increased coefficient of linear thermal expansion of products. In this regard, a promising area of research is to study the effect of aluminum phosphate additives on the properties of quartz ceramics. According to the totality of properties, the addition of AlPO4 in an amount of 20 wt % has the most positive effect on the characteristics of quartz ceramics. According to differential thermal analysis, it is noted that up to a temperature of 1,200 °C, no noticeable phase and modification transformations occur in the base mixtures. In the course of the work, it was found that the most appropriate firing mode is as follows: oxidizing medium; the products are immersed in a hot furnace, after being held at the maximum temperature, they are removed from the hot furnace, cooling occurs slowly in the air. The materials obtained in this way are characterized by the following properties: α=31.6·10-7 deg-1; σcomp=153 MPa; P=2.7 %; tgδ and ε (frequency 1010 Hz, temperature 20 °C) 0.001 and 10, respectively. It is noted that the main crystal phase prevailing in the samples is aluminum phosphate. The microstructure of the material is characterized by the presence of a small number of residual pores and a densely sintered shard. The proposed solution will significantly reduce power consumption, improve production performance and increase the basic properties of polyfunctional quartz ceramic products